Randomized clinical trial of ICECaP (Individualized Coordination and Empowerment for Care Partners of Persons with Dementia): Primary mental health and burden outcomes - Virginia T. Gallagher; Anna Arp; Ryan Thompson; M. Agustina Rossetti; James Patrie; Shannon E. Reilly; Carol Manning (PLoS ONE, 2025)
We examine the efficacy of the Individualized Coordination and Empowerment for Care Partners of Persons with Dementia (ICECaP), an intervention that involves one-on-one individualized support from a dementia care coordinator for a dementia care partner, compared to an active control group. At least once monthly contact is made from a dementia care coordinator to the dementia care partner by telephone, video conferencing, email, or in-person support at clinical visits for the person with dementia. In this pilot randomized unblinded control trial of ICECaP, n = 61 (n = 90 randomized) care partners completed 12-months of the ICECaP intervention and n = 69 (n = 92 randomized) care partners received routine clinical support (controls) in an outpatient memory care clinic at an academic medical center, from which the participants were recruited. Early termination endpoints (death and higher level of care) and trial drop out were comparable across groups. Primary efficacy outcomes were evaluated by comparing changes in care partner mental health, burden, and quality of life from baseline to 12-months between ICECaP and controls. Linear mixed-effects model with covariate adjustment revealed no significant group differences in longitudinal changes on measures of caregiving burden, care partner depression, anxiety, quality of life, or reactions to the behavioral symptoms of the person with dementia. Hypothesized reasons for lack of initial efficacy on primary 12-month outcomes are discussed.